**If an equation has brackets in it one method of solving it is to multiply out the brackets first, for example:**

**Solve the equation 3(b + 2) = 15**

**Write down the equation:**
**3(b + 2) = 15**

**Multiply out the brackets. Remember, everything inside the brackets gets multiplied by 3**
**3 × b + 3 ×2 = 15**

**When you have multiplied out the brackets you get:**
**3b + 6 = 15**

**Next, undo the + 6. In other words, do the inverse and subtract 6 from both sides.**
**3b + 6 - 6 = 15 - 6**
**So 3b = 9**

**Therefore, to find out what b is you need to do the inverse of multiplying by 3 which is dividing by 3.**

**So b = 3**

## Comments